Improving Student Achievement through Think Pair Share in Informatics Learning: Meningkatkan Prestasi Siswa Melalui Metode Think Pair Share dalam Pembelajaran Informatika - Hodri; Hasanah, Fitriah Nur (Indonesian Journal of Education Methods Development, 2025)
Background: Ineffective learning conditions in grade VIII B students have led to passive engagement and low outcomes in Informatics, especially in application software and office applications topics. Specific Background: Traditional teaching approaches used in the classroom did not sufficiently promote student participation or independent thinking. Knowledge Gap: Although TPS has been widely applied in other subjects, its implementation in Informatics learning in MTs Negeri Gresik had not been examined. Aim: This study aimed to improve student learning outcomes through the Think Pair Share model. Results: Using a one-cycle classroom action research design, student mastery improved from an average pre-cycle score of 69.17 to 76.94, while class completion increased from 44% to 72%. A total of 22 students showed individual improvement. Novelty: This research provides specific insight into using TPS to strengthen understanding of application software and office applications in Islamic junior secondary education settings. Implications: The findings indicate that TPS can be an effective cooperative strategy for Informatics learning, and its structured stages may support improved cognitive performance and classroom participation. Highlights:• Increased mastery in Informatics learning• Successful application of TPS in MTs context• Data-supported improvement in student outcomes Keywords: Think Pair Share, Informatics Learning, Student Achievement, Cooperative Learning, Application Software